A rare case of pyogenic pericarditis secondary to Streptococcus constellatus. (28th March 2018) - Ghazala, Sehem; Golden, Todd Rabkin; Farran, Sumaya; Zangeneh, Tirdad T
Abstract : We report an extremely rare case of purulent pericarditis caused by the normally commensal oral flora, Streptococcus constellatus, a viridans Streptococcal species and member of the S. anginosus group (previously also known by the eponymous ' S. milleri', for American Willoughby Dayton Miller). This case is a previously healthy 71-year-old immunocompetent woman from Arizona who presented with a 5-day history of progressive shortness of breath and chest tightness, and subjective fever and chills, but without history of nausea, vomiting, night sweats, recent travel, autoimmune disease or sick contacts. Early recognition and intervention of purulent pericarditis allow patients like the one outlined in this case to achieve full recovery.